Addressing Reproductive Issues in Semi-Intensive Dairy Cow Rearing - A Kannagi, Intekhab Alam, Rahul Bhatt (Revista Electronica de Veterinaria, 2024)
Small and marginal farmers engage in a semi-intensive type of dairy cattle production in the Manipur area of North-Eastern India. The study attempted to determine the prevalence of reproductive problems that are important for agricultural dairy cattle production. In crossbred dairy cattle, namely the Jersey crosses (JCB) and Holstein Friesian crosses (HFCB) breeds, the main objective waste ascertain the frequency of significant reproduction problems. An in-depth analysis of 620 crossbred dairy cattle from 10 districts of Manipur was over the course of 2 years (2021-2022). Among them were 230 HFCB and 390 JCB. The goal of the analysis was to determine the prevalence of significant clinical reproductive issues, with a focus on anestrus, abortion, repeat breeding and fetal membrane retention. Additionally, investigations were conducted into minor reproductive issues such pyometra (PY), endometritis (EDM), prolapsed (PL) and dystocia (DS). To identify patterns and variances, the data were further segmented by breed, age and parity. Of all the animals evaluated, 34.96% (n=225) had at least one clinical reproductive issue. The primary reproductive issues found were Anestrus (AN) (31.98%), abortion (10.36%), retention of fetal membrane (RFM) (12.46%) and repeated breeding (24.92%). PL (2.64%), EDM (5.72%), PY (7.55%) and DS (4.23%) were among the minor reproductive issues. Notable variations in the prevalence of reproductive illnesses according to the same level, species and its age were found in the analysis. The results of the study demonstrate the occurrence on significant reproductive issues in dairy cattle produced in Manipur by small and marginal farmers in a semi-intensive system.